2013
DOI: 10.1111/cpf.12115
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of linear and nonlinear heart rate dynamics after coronary artery bypass grafting surgery

Abstract: Our data suggest that patients submitted to OPCAB and an inpatient CR programme present with greater improvement in CA function compared to C-CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…However, nonlinear indices have been shown to be better than conventional methods for identifying subtle changes in cardiac autonomic modulation in various pathological conditions such as cardiovascular artery disease. 39 Nonlinear analysis has provided new insight into the HRV dynamics in various physiological and pathophysiological conditions, providing additional prognostic and analytical information to conventional approaches. 40 In the currently study, nonlinear indices were found to be reduced in the DMT2+HTN group when compared to the DMT2 group.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonlinear indices have been shown to be better than conventional methods for identifying subtle changes in cardiac autonomic modulation in various pathological conditions such as cardiovascular artery disease. 39 Nonlinear analysis has provided new insight into the HRV dynamics in various physiological and pathophysiological conditions, providing additional prognostic and analytical information to conventional approaches. 40 In the currently study, nonlinear indices were found to be reduced in the DMT2+HTN group when compared to the DMT2 group.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that should be observed refers to the HRV analysis during physical exercise as the increase in the respiratory rate shifts the high frequency (HF) band of the spectral analysis to the right, changing the bands in which they are to be analysed. 50 Another condition is the HRV spectral analysis of patients resting in the recent postoperative period (e.g., 1st and 2nd postoperative days of myocardial revascularisation surgery) because the presence of a high respiratory rate is very frequent in this condition 7,17 and this may also contribute to shifting the HF band. In this case, the processing software should allow the upper limit of the high frequency band to be extended, e.g.…”
Section: Comments/suggestionsmentioning
confidence: 99%
“…CABG produces an important negative impact on autonomic cardiac function [ 13 , 14 ] and RMS [ 15 ] . Previous studies have reported that return of RMS takes several months following CABG [ 16 ] .…”
Section: Introductionmentioning
confidence: 99%